2020
DOI: 10.25015/16202027574
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the Adoption of Beef Cattle Artificial Insemination (AI) Technology in Brebes Regency

Abstract: Efforts to increase beef cattle population and genetic in Brebes Regency can be done by using artificial insemination (AI) technology approach.Therefore this study aims to determine the factors that influence the ability of beef cattle farmers in adopting artificial insemination technology (AI) in Brebes Regency. Survey method was applied to observe beef cattle and farmers. Sampling technique used Slovin formula with 90% significant rate to observe variables, namely the ability of farmers to adopt AI technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…It may also turn out that these muturu breeders have a good knowledge of the importance of genetic improvement and prevention of genital diseases that AI can bring to their herd and hence CAP selection. This is in contrast to the findings of Setiana et al (2020), who reported that owned herd size was not significant for the decision to adopt innovation (IA) in Brebes. Onoh et al (2012) believe that farm size affects the extent to which farmers will adopt innovation and are willing to pay for such services.…”
Section: Determinants Of Willingness To Pay For Artificial Inseminati...contrasting
confidence: 99%
“…It may also turn out that these muturu breeders have a good knowledge of the importance of genetic improvement and prevention of genital diseases that AI can bring to their herd and hence CAP selection. This is in contrast to the findings of Setiana et al (2020), who reported that owned herd size was not significant for the decision to adopt innovation (IA) in Brebes. Onoh et al (2012) believe that farm size affects the extent to which farmers will adopt innovation and are willing to pay for such services.…”
Section: Determinants Of Willingness To Pay For Artificial Inseminati...contrasting
confidence: 99%
“…Experience, knowledge, and skills increase according to age (Eddy, Roessali, & Marzuki, 2012). In contrast, other studies showed that aged farmers had less motivated to develop farming, while young farmers were interested to change and adopt technology (Setiana, Saleh, Nugroho, & Lana, 2020). Supporting this, the result of this study showed that the age of respondents affected the ability of innovation adoption.…”
Section: Respondent Characteristicssupporting
confidence: 58%
“…Similar to the age of respondents, the education level of farmers and its impact on the adoption level differs for every case. Some previous research found that education level was not significantly related to the adoption rate of innovation (Setiana et al, 2020;Sirajuddin, Sudirman, Bahar, Al Tawaha, & Al Tawaha, 2018). However, the higher level of education had higher innovation adoption levels compare to farmers with a lower level of education (Soekartawi, 2008).…”
Section: Respondent Characteristicsmentioning
confidence: 95%
“…Knowing the factors that influence the success of AI in cattle is very important for farmers to increase the efficiency and productivity of their livestock (Müller-Sepúlveda et al 2020). The selection of the right factors and the application of the right steps will provide an opportunity to increase the success of AI (Setiana et al 2020), resulting in high-quality, productive, and profitable cattle populations. Several studies related to this topic have been conducted in various regions but have never been conducted in Langsa City.…”
Section: Introductionmentioning
confidence: 99%